Asthma control and action plans. Issue 6 (7th December 2017) - Kouri, Andrew; Boulet, Louis-Philippe; Kaplan, Alan; Gupta, Samir
Arguments over semantics will not advance our common goal of improving AAP uptake http://ow.ly/rSaq30fRila We would like to thank I. Amirav and M.T. Newhouse for their correspondence in response to our recent paper, "An evidence-based, point-of-care tool to guide completion of asthma action plans in practice" [1]. They raise an important issue surrounding confusion between the concepts of poor baseline asthma control and acute changes in symptoms that merit activation of the "yellow zone" of the asthma action plan (AAP). Although, contrary to their contention, this discussion does not affect the objective or outcome of our analysis, which was to provide a practical, evidence-based guide to populating the AAP yellow zone, it merits further discussion.